Effect of Selected Economic Sectors on Poverty - Cut Miranda Pusra; Srinita Srinita; Chenny Seftarita (International Journal of Business, Economics, and Social Development, 2021)
This study analyzes the influence of certain economic sectors on poverty levels in districts/cities in Aceh Province. The determination of the economic sector is based on the 4 largest contributions to the economy in Aceh. The economic sector in question is the agriculture, trade, construction, and processing industry sectors. So that the purpose of this study is to analyze the influence of selected economic sectors, namely the agricultural sector, the trade sector, the construction sector, and the manufacturing sector on poverty levels in Aceh. This study uses panel data from 23 districts/cities in Aceh Province for the period 2010-2019 and the data used is the percentage of poverty and data on the distribution of the percentage of Gross Regional Domestic Product (GRDP) by business field. The results obtained from this study are that all independent variables, namely the agricultural sector, the trade sector, the construction sector, and the manufacturing sector have a significant negative effect on the poverty level. This can be seen from the F test probability of 0.00. partially the agricultural sector reduced the poverty rate by 0.71 percent. trade sector 0.48 percent. the construction sector reduces poverty by 0.51 percent and the manufacturing sector reduces poverty by 0.67 percent. Therefore, it is hoped that the government can work together with other policymakers to improve the manufacturing sector both in agriculture and other fields to increase the productivity of society to alleviate poverty.